Demand for lottery products : a cross country analysis - Kaizeler, Maria João (2008)
Varieties of lottery games are played regularly in more than half of the world's countries. When considering the probability of winning a lottery jackpot, we have a sense of the illogicality in buying a lottery ticket. This begs the question, why do people buy lottery products? This paper investigates the socio-economic and demographic features that help to explain the behavioural trend of lottery product purchasing throughout the world. With a multivariate linear regression analysis, this study uses macroeconomic data and qualitative variables to explain the variation of a country's per-capita lottery sales. Some very interesting results were obtained. For example, the higher a country's level of education, percentage of males and Christians, the higher are the lottery sales. The relationship between lottery sales and per-capita GDP is an inverted U: lottery sales increase simultaneously with increases in per-capita GDP up to a point and then start to decrease. These results are of interest because they suggest a link between certain socio-economic and demographic characteristics and consumer behaviour and may give a boost to the use of these characteristics in consumer research.